Muscidae (Insecta: Diptera) of Latin America and the Caribbean: geographic distribution and check-list by country - Löwenberg-Neto, Peter; de Carvalho, Claudio J.b. (Zootaxa, 2013)
Here we provide a geographic database for the Muscidae (Insecta: Diptera) that are endemic to Latin America and the Caribbean and non-synanthropic. We summarize the geographic information provided by specimens from three entomological collections in Brazil (DZUP, MNRJ, and MZUEFS) as well as geographic information we compiled in the literature. The resulting 817 species were linked to their geographic records by country, state/province/department, locality, latitude and longitude, including source reference. When coordinates were not provided in specimens’ labels, we used the locality information to search geographic coordinates in online gazetteers. We also separated the species by country for a country-species list. These data comprise 250 years of collections and taxonomic studies of Neotropical Muscidae and we expect that it provides a foundation and serves as guide for future studies of systematics and biogeography of the family.